CSF total tau/α‐synuclein ratio improved the diagnostic performance for Alzheimer's disease as an indicator of tau phosphorylation. (31st December 2021) - Kang, Min Ju; Shim, Kyu Hwan; Suh, Jeewon; Pyun, Jung Min; Ryoo, Nayoung; Park, Young Ho; Youn, Young Chul; Jang, Jae‐Won; Jeong, Jee Hyang; Park, Kyung Won; Choi, Seong Hye; Suk, Kyoungho; et al.
Abstract: Background: Recently, several studies suggested potential involvements of α‐synuclein in Alzheimer's disease (AD) pathophysiology. Higher concentrations of α‐synuclein were reported in cerebrospinal fluid (CSF) of AD patients with a positive correlation towards CSF tau, indicating its possible role in AD. We analyzed the CSF biomarkers to verify whether α‐synuclein could be an additional supported biomarker in AD diagnosis. Method: In this cross‐sectional study, CSF samples of 71 early‐onset AD, 34 late‐onset AD, 11 mild cognitive impairment, 17 subjective cognitive decline, 45 Parkinson's disease, and 32 healthy control (HC) were collected. CSF amyloid‐β1‐42 (A), total tau (N), and phosphorylated tau181 (T) were measured by commercial ELISA kits, and in‐house ELISA kit was developed to quantify α‐synuclein. The cognitive assessments and amyloid‐PET imaging were also performed. Result: CSF α‐synuclein manifested a tendency to increase in AD and to decreased in Parkinson's disease compared to HC. The equilibrium states of total tau and α‐synuclein concentrations were changed significantly in AD, and the ratio of total tau/α‐synuclein (N/αS) was dramatically increased in AD than HC. Remarkably, N/αS revealed a strong positive correlation with tau phosphorylation rate. Also, the combination of N/αS with amyloid‐β1‐42/phosphorylated tau181 had the best diagnosis performance (AUC = 0.956, sensitivity = 96%, specificity = 87%). In concordance analysis, N/αS showed the higher diagnostic agreement with amyloid‐β1‐42 and amyloid‐PET. Analysis of biomarker profiling with N/αS had distinctive characteristics and clustering of each group. Especially, among the group of suspected non‐Alzheimer's disease pathophysiology, all A‐T+N+ patients with N/αS+ were reintegrated into AD. Conclusion: The high correlation of α‐synuclein with tau and the elevated N/αS in AD supported the involvement of α‐synuclein in AD pathophysiology. Importantly, N/αS improved the diagnostic performance, confirming the needs of incorporating α‐synuclein as a biomarker for neurodegenerative disorders. The incorporation of a biomarker group [N/αS] could contribute to provide better understanding and diagnosis of neurodegenerative disorders.